The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Predictability of spatial distribution of pre-summer extreme precipitation days over southern China revealed by the physical-based empirical model - Juan Li; Changshan Zheng; Ying Yang; Rui Lu; Zhiwei Zhu (Climate Dynamics, 2023)

Enhancement of the summer extreme precipitation over North China by interactions between moisture convergence and topographic settings - Yang Zhao; Deliang Chen; Jiao Li; Dandan Chen; Yi Chang; Juan Li; Rui Qin (Climate Dynamics, 2020)
This study investigates the roles of atmospheric moisture transport under the influence of topography for summer extreme precipitation over North China (NC) during 1979–2016. Based on rain gauge precipitation data and a reanalysis, 38 extreme precipitation days in NC during the 38 years were selected and associated moisture fluxes estimated. The results show that there is a dominant moisture influx of 311.8 kg m −1 s −1 into NC along its southern boundary from tropical oceans, and a secondary influx of 107.9 kg m −1 s −1 across its western boundary carried by mid-latitude westerlies. The outflux across the eastern boundary is 206.9 kg m −1 s −1 and across the northern boundary is 76.0 kg m −1 s −1 , giving a net moisture gain over NC of 136.8 kg m −1 s −1 . During extreme precipitation days, the moisture flux convergence (MFC) was much larger, exceeding 4 × 10 −5 kg m −1 s −1 . The MFC maximum core, the pronounced moisture transport, and the striking extreme precipitation zone over NC are all anchored to the east of the steep slopes of the surrounding topography. Moreover, a remarkably high humidity and strong upward motion also occur near steep slopes, indicating the critical role of the adjacent topography on the extreme precipitations. Simulations with and without the topography in NC using the Weather and Research Forecasting model for six selected out of the 38 extreme precipitation days demonstrate that the surrounding topography reinforces the MFC over NC by 16% relative to the case without terrain, primarily through enhanced wind convergence and higher moisture content, as well as stronger vertical motion induced by diabatic heating. The interactions between moisture convergence and topographic settings strengthen the extreme precipitation over NC.

Boreal winter Arctic Oscillation as an indicator of summer SST anomalies over the western tropical Indian Ocean - Dao-Yi Gong; Dong Guo; Yongqi Gao; Jing Yang; Rui Mao; Jingxuan Qu; Miaoni Gao; Sang Li; Seong-Joong Kim (Climate Dynamics, 2017)